Use of Auditory Training and Its Influence on Early Cochlear Implant Outcomes in Adults. Issue 2 (February 2022) - Dornhoffer, James R.; Reddy, Priyanka; Ma, Cheng; Schvartz-Leyzac, Kara C.; Dubno, Judy R.; McRackan, Theodore R.
Abstract : Objective: Assess associations between postcochlear implant (CI) auditory training and early outcomes related to speech recognition and CI quality of life (CIQOL). Study Design: Longitudinal, prospective cohort. Setting: Tertiary academic center. Patients: Seventy-two adults undergoing cochlear implantation for bilateral severe-to-profound hearing loss. Interventions: Self-reported use of three categories of auditory training post-CI activation: (1) face-to-face training (e.g., speech pathologist), (2) passive home-based training (e.g., listening to audiobooks), and (3) computer-based training (e.g., interactive software). Main Outcome Measures: Change in Consonant-Nucleus-Consonant phoneme (CNCp), CNC word (CNCw), AzBio sentences in quiet, and CIQOL-35 Profile global and domain scores from pre-CI to 3-month post-CI. Results: Of 72 patients, 52 (72.2%) used an auditory training resource. Of all patients, 18.4% used face-to-face training, 58.3% passive home-based training, and 33.3% computer-based training. At 3 months post-CI, use of any training was associated with greater improvement in speech recognition ( d- range = 0.57–0.85) and global and domain-specific CIQOL scores, except entertainment ( d- range = −0.33 to 0.77). Use of computer-based training demonstrated the greatest effect, with larger improvements in speech recognition (CNCp: d  = 0.69[0.03, 1.35]; CNCw: d  = 0.80[0.14, 1.46]; AzBio: d  = 1.11[0.44, 1.77]) and global and all domain-specific CIQOL scores ( d- range  =  0.05–1.35). Controlling for age, sex, household income, and use of multiple training resources, computer-based training remained the strongest positive predictor of speech recognition and CIQOL improvement, with significant associations with CNCp (ß = 33.07[1, 43, 64.719]), AzBio (ß = 33.03[5.71, 60.35]), and CIQOL-global (ß = 10.92[1.15, 20.70]) score improvement. Conclusions: Our findings provide preliminary evidence-based recommendations for use of specific auditory training resources for new adult CI recipients. Auditory training, especially self-directed computer software, resulted in improved speech recognition and CIQOL outcomes after 3 months and are widely available for CI users.